Integrated water resource management to address the growing demand for food and water in South Asia. (28th March 2021) - Birendra, KC; McIndoe, Ian; Schultz, Bart; Prasad, Krishna; Bright, John; Dark, Andrew; Prasad Pandey, Vishnu; Chaudhary, Anubhav; Thapa, Prithbi Man; Perera, Rohan; Dangi, Dillee Ram
Abstract: With the increasing population and accelerated urbanization, demands for water are rising for different sectors around the world, including in South Asia. Integrated water resource management (IWRM) offers a promising potential to address multifaceted water demands. This study therefore aimed to address this issue by (i) reviewing key issues related to water, land, and food in South Asian countries, (ii) exploring the prevalent irrigation management strategies in those countries, and (iii) examining the IWRM situation based on a Nepalese case study, and it proposes some options to support effective implementation of IWRM. South Asia, the home to 24% of the world's population with only 15% and 7% of the world's arable and permanent crop land and water resources, respectively, is the worst‐affected region in the world from undernourishment. Surface irrigation is the dominant irrigation application method in the region, which incurs high water losses due to the lack of flexible water control structures in canal networks. The Nepalese case study revealed a lack of clear institutional arrangements to implement IWRM and disparate and conflicting views about IWRM. Creation and strengthening of basin‐level water user organizations, technological improvements, and awareness‐raising activities are some potential ways forward to implement IWRM. RÉSUMÉ: Avec l'augmentation de la population et l'urbanisation accélérée, la demande en eau augmente pour différents secteurs à travers le monde, y compris en Asie du Sud. La gestion intégrée des ressources en eau (GIRE) offre un potentiel prometteur pour répondre aux multiples demandes en eau. Cette étude visait donc à résoudre ce problème en: i) passant en revue les principaux problèmes liés à l'eau, à la terre et à l'alimentation dans les pays d'Asie du Sud; ii) explorer les stratégies de gestion de l'irrigation qui prévalent dans ces pays; iii) examiner la situation de la GIRE sur la base d'une étude de cas au Népal et proposer quelques options pour soutenir la mise en œuvre efficace de la GIRE. L'Asie du Sud, qui abrite 24% de la population mondiale mais qui ne possède respectivement que 15 et 7% des terres arables et des terres agricoles permanentes et des ressources en eau du monde, est la région du monde la plus touchée par la sous‐alimentation. L'irrigation de surface est la méthode d'application d'irrigation dominante dans la région, qui entraîne des pertes d'eau élevées en raison du manque de structures flexibles de contrôle de l'eau dans les réseaux de canaux. L'étude de cas du Népal a révélé un manque d'arrangements institutionnels clairs pour mettre en œuvre la GIRE et des points de vue disparates et contradictoires sur la GIRE. La création et le renforcement des organisations d'usagers de l'eau au niveau du bassin, les améliorations technologiques et les activités de sensibilisation sont des moyens potentiels de mettre en œuvre la GIRE.